Surviving the tides, the bumps and the jolts in democracy : building a solid anti-corruption framework to create a ‘useful’ Nigeria - Bamidele, Seun (Penerbit Universiti Kebangsaan Malaysia, 2018)
It is no exaggeration of the tragic events that have taken place in the country since independence, to say that all efforts to establish efficient public institutions have been frustrated by corruption. The general consensus is that all public office holders are culprits, and as such, it would be impossible to eradicate corruption. In order for this present democratic government to forge ahead in its fight against the pervasive, corrupt administration in Nigerian, and in a bid to dislodge itself from the cankerworm of corruption in public institutions, it is working tirelessly to eradicate corruption. This article discusses the curbing of the menace, corruption in Nigeria, by carrying out a critical analysis and assessment of the current Nigerian President, Muhammadu Buhari’s democratic government and his anti-corruption war as enacted in the last two years, and how viable and visible it has been.